How the compensation gap between median full-time non-managerial employees and executives affects audit quality: Evidence from the Big 4 accounting firms - Yu-Ting Huang (International Journal of Business and Economic Sciences Applied Research (IJBESAR), 2024)
Purpose: Studies have relied on full-time non-managerial employees' average compensation to measure pay disparities. However, this approach can be distorted by outliers. Instead, median compensation has the potential to more accurately reflect employee compensation. This study examines how the gap between full-time non-managerial time employees' average compensation and executive compensation affects Taiwanese public companies' audit quality. Additionally, it analyzes how this relationship is influenced by the type of accounting firm and management team stability. Design/methodology/approach: This study focuses on publicly listed companies in Taiwan from 2019 to 2023. It investigates whether a greater gap between the median compensation of full-time NMEs and executive compensation-indicating a compensation structure favoring higher-level employees-correlates with higher audit and non-audit fees. Data were obtained from the Market Observation Post System and Taiwan Economic Journal financial database. For STATA statistical software to simplify the computations in ordinary least squares. Findings: In companies audited by the Big 4 accounting firms, a wider gap between full-time non- managerial employees' median compensation and executive compensation is associated with higher audit fees. Thus, such companies have greater operational complexity and more advanced risk management, which in turn raises audit costs. Specifically, these companies may have higher earnings management risk, thus necessitating more extensive audit resources. Furthermore, the Big 4 firms' strong brand reputation, higher audit quality, and larger market share allow them to charge premium rates. This illustrates the differentiated pricing strategies and competitive dynamics within this market segment. Additionally, companies with stable management teams-where executives have remained in position for at least three years-tend to more effectively implement professional development programs. They also demand a higher level of both audit and non-audit services, demonstrating a willingness to invest in substantial audit and non-audit fees to ensure professionalism and integrity in the auditing process. Research limitations/implications: The findings carry significant practical implications for audit firm pricing strategies, and for companies in choosing auditors and allocating resources. Companies should consider their own operational complexity, risk management level, and management stability to select the most suitable audit services and Big 4 accounting firm. Originality/value: This study offers several key contributions. It innovatively uses median, not average, non- managerial employee compensation to measure the pay gap, thus avoiding distortion from outliers. The impact of this refined measure on both audit and non-audit fees is examined, providing a more comprehensive understanding of audit pricing. Furthermore, it distinguishes between Big 4 and non-Big 4 firms, revealing firm-specific pricing strategies. Finally, management stability is included as a moderator, highlighting its role in the relationship between compensation structure, audit quality, and organizational stability. The findings offer valuable insights for audit firms, companies, and stakeholders concerning pricing, auditor selection, and the importance of fair compensation for corporate social responsibility.
Keywords: M41; M42; 330; audit fees; non-audit fees; Big 4 Accounting Firms; compensation gap between median full-time non-managerial employees and executives